Penetration of anthropophytes into alluvial phytocoenoses of the Skawica river valley (western Carpathians) - Uziębło, Aldona K. (Biodiversity: Research and Conservation, 2008)
In this paper, data on penetration of anthropophytes into alluvial phytocoenoses, collected in the years 2006-2007, were analysed with reference to the level of their disturbance, community structure and localization of patches. The investigation was carried out in the whole Skawica valley (in the area comprising villages Zawoja, Skawica and Białka). On the basis of 106 phytosociological relevés, eight associations were distinguished: Rorippo-Agrostietum, Phalarido-Petasitetum hybridi, Filipendulo ulmariae-Menthetum longifoliae, Phalaridetum arundinaceae, Glycerietum plicatae, Thyphetum latifoliae, Alnetum incanae, Salicetum albo-fragilis. It was stated that phytocoenoses undisturbed or less disturbed are penetrated with anthropophytes in smaller degree while riparian forest associations are more threated by anthropophytes. Invasive species – Impatiens glandulifera, Impatiens parviflora and Reynoutria japonica – most frequently penetrate phytocoenoses of Alnetum incanae, Salicetum albo-fragilis, Phalarido-Petasitetum hybridi and Filipendulo ulmariae-Menthetum longifoliae. Communities which are free from penetration by anthropophytes in this area include rush associations: Glycerietum plicatae and Typhetum latifoliae.